2014
DOI: 10.1016/j.biopsych.2013.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Immune System Disturbances in Schizophrenia

Abstract: Epidemiological, genetic, transcriptome, postmortem, peripheral biomarker, and therapeutic studies of schizophrenia all point to a dysregulation of both innate and adaptive immune systems in the disease, and it is likely that these immune changes actively contribute to disease symptoms. Gene expression disturbances in the brain of subjects with schizophrenia show complex, region-specific changes with consistently replicated and potentially interdependent induction of serpin peptidase inhibitor, clade A member … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
130
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(134 citation statements)
references
References 93 publications
1
130
3
Order By: Relevance
“…Any disruption could offset, alter, or cease these coordinated processes with immediate, delayed, or cascading consequences on brain function and alter the trajectory of development . Depending on the timing of the insult, common disruptions could have transient effects or marked and compounding consequences that lead to chronic disability (Horvath and Mirnics, 2014a;Insel, 2010;Lewis and Levitt, 2002). Furthermore, the individual genetic makeup appears to be critical: the same insult can have minimal effect or a large effect in two different individuals, and this will largely depend on the disease-predisposing sequence variants in their genome (Horvath and Mirnics, 2014b).…”
Section: Development Of the Gabaergic Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Any disruption could offset, alter, or cease these coordinated processes with immediate, delayed, or cascading consequences on brain function and alter the trajectory of development . Depending on the timing of the insult, common disruptions could have transient effects or marked and compounding consequences that lead to chronic disability (Horvath and Mirnics, 2014a;Insel, 2010;Lewis and Levitt, 2002). Furthermore, the individual genetic makeup appears to be critical: the same insult can have minimal effect or a large effect in two different individuals, and this will largely depend on the disease-predisposing sequence variants in their genome (Horvath and Mirnics, 2014b).…”
Section: Development Of the Gabaergic Systemmentioning
confidence: 99%
“…However, determining causality can be difficult because of the protracted amount of time between insult and diagnosis . Immune system activation has been implicated as a risk factor for schizophrenia (Horvath and Mirnics, 2014a) and the major histocompatibility complex is the most prominent signal in GWAS studies (McAllister, 2014;Stefansson et al, 2009). MIA in rats and mice causes dysfunction of GABAergic circuitry in the hippocampus, amygdala, and cortex (Canetta and Brown, 2012;Meyer, 2014).…”
Section: Environmental Insults Disrupt Gabaergic System Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of cytokines and genes of the HLA region, critical components of the immune response, may be altered in peripheral immune cells and in glial cells of schizophrenic patients (Bernstein et al, 2015;Goudriaan et al, 2014;Miller et al, 2011;Sinkus et al, 2013). Several studies have shown a co-segregation of autoimmune diseases, chronic inflammation and maternal infection with schizophrenia (Bergink et al, 2014;Bernstein et al, 2015;Horvath and Mirnics, 2014;Knuesel et al, 2014;Stringer et al, 2014). This has led to the hypothesis that immunological disturbances are a key factor in the etiology of schizophrenia, notably through the role of microglial cells and astrocytes in the immune response in the brain (Bernstein et al, 2015;Horvath and Mirnics, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown a co-segregation of autoimmune diseases, chronic inflammation and maternal infection with schizophrenia (Bergink et al, 2014;Bernstein et al, 2015;Horvath and Mirnics, 2014;Knuesel et al, 2014;Stringer et al, 2014). This has led to the hypothesis that immunological disturbances are a key factor in the etiology of schizophrenia, notably through the role of microglial cells and astrocytes in the immune response in the brain (Bernstein et al, 2015;Horvath and Mirnics, 2014). While HLA proteins have been mainly studied for their roles in immunity, recent studies in rodents also point to functions in the neurons, notably of the MHC class I (MHCI) proteins (Boulanger, 2009;Elmer and McAllister, 2012;Lee et al, 2014;Shatz, 2009).…”
Section: Introductionmentioning
confidence: 99%